2007
DOI: 10.2139/ssrn.1025582
|View full text |Cite
|
Sign up to set email alerts
|

Science in the Jury Box: Jurors' Views and Understanding of Mitochondrial DNA Evidence

Abstract: Policy makers, pundits, and scholars have all raised questions about how jurors understand and apply scientific evidence. In the current study, 480 jury pool members observed a mock trial that included expert testimony about mitochondrial DNA (mtDNA)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…Across both studies we also found strong and consistent evidence that higher quality evidence is more persuasive than lower quality evidence. This result fits with previous research using rich representations of expert opinion quality (Martire et al, 2020 ) but is somewhat inconsistent with concerns about juror insensitivity to evidence quality (Cooper et al, 1996 ; Diamond and Rose, 2005 ; Hans et al, 2007 , 2011 ; McAuliff and Kovera, 2008 ; McAuliff et al, 2009 ; Koehler et al, 2016 ; Eldridge, 2019 ). In our studies, jurors were provided with information about an expert's field, their specialist background, their proficiency, the validity of their practicing domain, their trustworthiness, consistency with other experts, their supporting evidence and opinion clarity.…”
Section: Discussionsupporting
confidence: 83%
“…Across both studies we also found strong and consistent evidence that higher quality evidence is more persuasive than lower quality evidence. This result fits with previous research using rich representations of expert opinion quality (Martire et al, 2020 ) but is somewhat inconsistent with concerns about juror insensitivity to evidence quality (Cooper et al, 1996 ; Diamond and Rose, 2005 ; Hans et al, 2007 , 2011 ; McAuliff and Kovera, 2008 ; McAuliff et al, 2009 ; Koehler et al, 2016 ; Eldridge, 2019 ). In our studies, jurors were provided with information about an expert's field, their specialist background, their proficiency, the validity of their practicing domain, their trustworthiness, consistency with other experts, their supporting evidence and opinion clarity.…”
Section: Discussionsupporting
confidence: 83%
“…When case information is highly technical or scientific, there is a risk that jurors will find the evidence difficult to comprehend, thus increasing their likelihood of peripherally processing trial information (Hans, Kaye, Dann, Farley, & Albertson, 2011). Research has demonstrated that statistical and probabilistic evidence are particularly difficult for jurors to discern (Vidmar & Diamond, 2000) and that jurors consistently struggle to grasp the extent to which inferences can be drawn from DNA "match" evidence (Nance & Morris, 2005).…”
Section: Evidence Complexitymentioning
confidence: 99%
“…Ethical issues and concerns about horizontal equity make this approach infeasible, and have lead to the frequent use of mock jury trials in legal scholarship [Hans et al 2007].…”
Section: Analytic Frameworkmentioning
confidence: 99%
“…This interference has been coined the "CSI effect"; specifically, the use of forensic technology on crime dramas such as "CSI: Crime Scene Investigation" has limited prosecutors' ability to obtain a conviction without DNA or other forensic evidence. 4 To date, evidence on the CSI effect has been largely anecdotal [Toobin (2007); Stockwell (2005); Willing (2004)], or based on small surveys, either of potential jurors [Schweitzer and Saks (2007); Hans et al (2007); Podlas (2006)] or judges [Hughes and Magers (2007)]. Perhaps not surprisingly, reviews of the literature [Tyler (2006)] find no compelling evidence for or against the CSI effect.…”
Section: Introductionmentioning
confidence: 99%